Respostas

2014-03-22T20:04:28-03:00
V1=90km/h
v2=60km/h

vm=delta x/delta t  = vm=2x/t2+t1  eq 1

v1=x1/t1 = v1=x/t1 = t1=x/v1 eq 2

v2=x2/t2 = v2=x/t2   t2=x/v2 eq 3

substituindo 2 e 3 em 1

vm=2x          =          2x              =       2x(v1*v2)     =       2v1*v2   
       x + x             xv2 + xv1                 x(v2+v1)               v2+v1
      v1    v2              V1*v2

  vm=     2*90*60      =      10800     vm=72km/h
               90+60                    150
2 4 2
2014-03-22T20:45:40-03:00
Resposta

Como a distancia percorrida é a mesma vc pode usar esta formula

Vm = 2.V1.V2 / V1 + V2

Vm = 2.90.60 / 90 + 60

Vm = 10800 / 150

Vm = 72km/h

2 5 2